The short-term impacts of COVID-19 on the Malawian economy, 2020–2021: A SAM multiplier modeling analysis - Baulch, Bob; Botha, Rosemary; Pauw, Karl (International Food Policy Research Institute, 2020)
This paper has been written for the 2020 ECAMA Lakeshore Conference. It extends and updates the initial results of modeling undertaken by IFPRI to assess the short-run impacts of COVID-19 control measures on the Malawian economy. We also consider the short-run effects of external shocks associated with disruptions in trade and tourism, investment, and remittance flows on the Malawian economy, as well as two medium- erm paths assuming either faster or slower recovery during the remainder of 2020 and 2021. Using a SAM multiplier model, we estimate GDP declines by around 16.5 percent during April/May 2020 due to social distancing measures. This leads to around 1.6 million people, mainly in rural areas, temporarily falling into poverty, although urban households suffer the largest income losses.